Thomas Aquinas and Georg Hegel on the Trinity - Theron, Stephen, 1939- (Cambridge Scholars Publisher, 2020)
This book compares two Trinitarian studies, those of Hegel's and Aquinas's Trinitarian treatises, following upon Augustine's De trinitate. It distinguishes, regarding Hegel, doctrinal development of earlier texts from contradiction or false rationalisation (""logicisation"") thereof, or from their mere repetition. All separation of philosophy and theology is renounced, consistently with ""absolute idealism"" as defended here. Historical contexts are nonetheless respected in this book. Hegel, the profoundest Trinitarian philosopher-theologian since at least Aquinas, claims that ultimately ""rev